Recontextualizing Maulana Abul Kalam Azad’s Educational Philosophy for AI Ethics and Education - Saifullah; Saidul Amin; Deswita; Sukiyat; Dasman Yahya; Rina Rehayati; Dewi Cahyarani; Putri Angraini (RUSYDIAH: Jurnal Pemikiran Islam, 2026)
The increasing use of artificial intelligence (AI), particularly generative AI in educational contexts, raises epistemological and ethical questions concerning how knowledge is produced, evaluated, and used. This study recontextualizes Maulana Abul Kalam Azad’s philosophy of education as a framework for examining these challenges. Employing qualitative library research, the study combines hermeneutic interpretation, conceptual analysis, and philosophical recontextualization. Azad’s Tarjuman al-Qur’an and India Wins Freedom are examined alongside selected works on information philosophy, Islamic epistemology, AI ethics, and AI in education. The analysis reconstructs key dimensions of Azad’s epistemology concerning reason, revelation, knowledge, moral responsibility, and human development, and subsequently brings them into dialogue with contemporary challenges associated with AI-mediated education. The analysis suggests that computational efficiency and functional performance alone are insufficient criteria for educational knowledge and judgment. Based on this conceptual correspondence, the study develops a Synthetic Epistemology Model comprising three interconnected dimensions: technological intelligence, ethical judgment, and spiritual/value-oriented consciousness. The model positions AI as a technological instrument whose educational significance depends on human interpretation, ethical oversight, and the purposes guiding its use. The study does not claim that Azad anticipated contemporary AI; rather, it proposes a normative recontextualization of his epistemological principles for current educational challenges. The study contributes a philosophical framework for integrating technological capability with critical reasoning, ethical responsibility, and human development in AI-mediated education.